(untitled) (2012)
The nucleation energy of bimetallic MCu n clusters (MNi. Pd, Pt; n = 1-4) adsorbed on an F s center of the MgO(001) surface have been studied by first-principles method based on density functional theory and compared to their gas phase counterparts. In addition, the condensed Fukui function and the interaction with a single H atom as a test probe are investigated as possible descriptors of the chemical reactivity of these supported bimetallic clusters. It was found that both, nucleation energy and chemical reactivity present odd-even oscillations in the free and supported clusters; these oscillations are related to the electronic nature of the open/closed shell nature of the electronic ground state. Also, it was found that the chemical reactivity depends on the atom (M or Cu) that is directly above the vacancy. When the bonding is done through the Cu atom, the chemical reactivity is larger than when it is bound through the M atom. It was also found that the presence of the underlying substrate largely influences the reactivity site nature of Cu nM clusters. © 2012 Elsevier B.V.